A Two-Tiered Earnings Frontier Estimation of Employer and Employee Information in the Labor Market - Polachek, Solomon W.; Yoon, Bong Joon (The Review of Economics and Statistics, 1987)
Solomon W. Polachek, Bong Joon Yoon, A Two-Tiered Earnings Frontier Estimation of Employer and Employee Information in the Labor Market, The Review of Economics and Statistics, Vol. 69, No. 2 (May, 1987), pp. 296-302